ABET-Compliant Training Program Implementation Impact on Improvement of Training Quality - Le, Nhat Duy (Journal of Technical Education and Training, 2025)
Improving engineering education quality is essential to meet modern labor market demands and enhance global competitiveness. Accreditation by the Accreditation Board for Engineering and Technology (ABET) is widely recognized as a benchmark for high-quality educational programs. Despite ABET’s international prominence, limited research explores its impact on Vietnamese universities, particularly in adapting curricula to international standards. This study assesses the impact of ABET accreditation on the quality of education at the Industrial University of Ho Chi Minh City (IUH), a prominent Vietnamese institution striving to align with global standards, while contextualising its findings within the broader regional and international landscape. A mixed-methods approach was employed, including surveys of 500 students and 60 faculty members, comparative analyses of pre- and post-accreditation data, and statistical evaluations of key indicators such as GPA, publication rates, and employment statistics. Implementing ABET standards led to significant improvements in education quality at IUH. Average GPAs, initially reflecting a borderline neutral/disagree stance (2.7), improved slightly to 2.9, moving towards agreement. Additionally, student satisfaction increased from 60% to 75%, and faculty satisfaction grew from 73% to 82%, indicating notable enhancements in perceived quality. ABET accreditation proved transformative, bridging academia-industry gaps and preparing students for global careers. Sustaining these outcomes requires ongoing curriculum refinement, stakeholder engagement, and resource investment.